Boron deficiency in woody plants: various responses and tolerance mechanisms - Wang, Nannan; Yang, Chengquan; Pan, Zhiyong; Liu, Yongzhong; Peng, Shu’ang (Frontiers in Plant Science, 2015)
Boron (B) is an essential microelement for higher plants, and its deficiency is widespread around the world and constrains the productivity of both agriculture and forestry. In the last two decades, numerous studies on model or herbaceous plants have contributed greatly to our understanding of the complex network of B-deficiency responses and mechanisms for tolerance. In woody plants, however, fewer studies have been conducted and they have not well been recently synthesized or related to the findings on model species on B transporters. Trees have a larger body size, longer lifespan and more B reserves than do herbaceous plants, indicating that woody species might undergo long-term or mild B deficiency more commonly and that regulation of B reserves helps trees cope with B deficiency. In addition, the highly heterozygous genetic background of tree species suggests that they may have more complex mechanisms of response and tolerance to B deficiency than do model plants. Boron-deficient trees usually exhibit two key visible symptoms: depression of growing points (root tip, bud, flower, and young leaf) and deformity of organs (root, shoot, leaf, and fruit). These symptoms may be ascribed to B functioning in the cell wall and membrane, and particularly to damage to vascular tissues and the suppression of both B and water transport. Boron deficiency also affects metabolic processes such as decreased leaf photosynthesis, and increased lignin and phenol content in trees. These negative effects will influence the quality and quantity of wood, fruit and other agricultural products. Boron efficiency probably originates from a combined effect of three processes: B uptake, B translocation and retranslocation, and B utilization. Root morphology and mycorrhiza can affect the B uptake efficiency of trees. During B translocation from the root to shoot, differences in B concentration between root cell sap and xylem exudate, as well as water use efficiency, may play key roles in tolerance to B deficiency. In addition, B retranslocation efficiency primarily depends on the extent of xylem-to-phloem transfer and the variety and amount of cis-diol moieties in the phloem. The B requirement for cell wall construction also contribute to the B use efficiency in trees. The present review will provide an update on the physiological and molecular responses and tolerance mechanisms to B deficiency in woody plants. Emphasis is placed on the roles of B reserves that are more important for tolerance to B deficiency in trees than in herbaceous plants and the possible physiological and molecular mechanisms of differential B efficiency in trees. We propose that B may be used to study the relationship between the cell wall and the membrane via the B-bridge. Transgenic B-efficient tree cultivars have considerable potential for forestry or fruit rootstock production on low B soils in the future.